A terceira idade na universidade aberta: navegando, buscando, aprendendo em um mar sem fim - Pereira, Elizabeth Thomaz (2009)
This research aims to describe and interpret the phenomenon of learning for mature adults and elderly students in two Open University of The Third Age of São Paulo State. The purpose was to collect subsidies to be used in educating teachers for instructional contexts which aim at developing practices focused on education for that age group, providing the elderlies not only with integral development, but also equal opportunities and social inclusion. The relevance of this work is primarily, the worldwide growth interest in the social life of the elderly. This research discussed the increase in longevity in the world (Frias, 1998; Goldman, 2001; Kalache and Kickbusch, 1997; Veras, 1995), Gerontology (Cachioni, 2003; Hayflick, 1996; Neri, 1995; Papaléo Netto, 1996), Education (Canary, 2000; Case, 2000; Delors et al., 1999, Freire, 1996; Giubilei, 1993, Lima, 2001, Rogers, 1969; Sobral, 2001, Vygotsky, 1978), The Open Universities of The Third Age (Jordan Neto, 2001; Martins de Sá, 1991; Vella, 1997) and teacher education (Kenski, 2001, Monteiro, 2000, Moraes, 1997; Perrenoud, 2002) for those who are aging. To carry out the research, I used the hermeneutic-phenomenological approach (van Manen, 1990; Freire, 2007); including researching on interpretations of learning from students and teachers, mature adults and elderly, on this phase of their lives. In addition, this research tried to show what the nature of learning in old age in two Open Universities is. The gathered texts consisted of sixteen transcribed interviews with students and teachers, mature adults and elderly of two open universities. From the descriptions and interpretations of the experiences of these individuals, it was possible to identify the nature of the phenomenon. However, it should be emphasized that, throughout the interpretation process, the texts collected indicated that, against the initial intention, the target phenomenon was, in fact, the search in The Open University by senior citizens. When I reached the essence of the phenomenon, I identified the themes that structured this search, which are learning, welfare, pastime and relationships. These themes can be used as a basis for further researches. They can be and should continue being the prime objective of those who work or will work at institutions in which there are people from an age segment that most grows in the society we live